A Concise Review on the Role of CircPVT1 in Tumorigenesis, Drug Sensitivity, and Cancer Prognosis - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Taheri, Mohammad; Jamali, Elena (Frontiers in Oncology, 2021)
CircPVT1 (hsa_circ_0001821) is a cancer-related circular RNA (circRNA) that originated from a genomic locus on chromosome 8q24. This locus has been previously found to encode the oncogenic long non-coding RNA PVT1. Expression of this circRNA has been found to be upregulated in diverse neoplastic conditions. CircPVT1 acts as a sponge for miR-125a, miR-125b, miR-124-3p, miR-30a-5p, miR-205-5p, miR‐423‐5p, miR‐526b, miR-137, miR-145-5p, miR-497, miR-30d/e, miR-455-5p, miR-29a-3p, miR-204-5p, miR-149, miR-106a-5p, miR-377, miR-3666, miR-203, and miR-199a-5p. Moreover, it can regulate the activities of PI3K/AKT, Wnt5a/Ror2, E2F2, and HIF-1α. Upregulation of circPVT1 has been correlated with decreased survival of patients with different cancer types. In the current review, we explain the oncogenic impact of circPVT1 in different tissues based on evidence from in vitro, in vivo, and clinical investigations.